Take home injectable opioids for opioid use disorder during and after the COVID-19 Pandemic is in urgent need: a case study - Eugenia Oviedo-Joekes; Scott MacDonald; Charles Boissonneault; Kelli Harper (BMC, 2021)
Abstract Background In North America the opioid poisoning crisis currently faces the unprecedented challenges brought by the COVID-19 pandemic, further straining people and communities already facing structural and individual vulnerabilities. People with opioid use disorder (OUD) are facing unique challenges in response to COVID-19, such as not being able to adopt best practices (e.g., physical distancing) if they're financially insecure or living in shelters (or homeless). They also have other medical conditions that make them more likely to be immunocompromised and at risk of developing COVID-19. In response to the COVID-19 public health emergency, national and provincial regulatory bodies introduced guidance and exemptions to mitigate the spread of the virus. Among them, clinical guidance for prescribers were issued to allow take home opioid medications for opioid agonist treatment (OAT). Take Home for injectable opioid agonist treatment (iOAT) is only considered within a restrictive regulatory structure, specific to the pandemic. Nevertheless, this risk mitigation guidance allowed carries, mostly daily dispensed, to a population that would not have access to it prior to the pandemic. In this case it is presented and discussed that if a carry was possible during the pandemic, then the carry could continue post COVID-19 to address a gap in our approach to individualize care for people with OUD receiving iOAT. Case presentation Here we present the first case of a patient in Canada with long-term OUD that received take home injectable diacetylmorphine to self-isolate in an approved site after being diagnosed with COVID-19 during a visit to the emergency room where he was diagnosed with cellulitis and admitted to receive antibiotics. Conclusion In the present case we demonstrated that it is feasible to provide iOAT outside the community clinic with no apparent negative consequences. Improving upon and making permanent these recently introduced risk mitigating guidance during COVID-19, have the potential not just to protect during the pandemic, but also to address long-overdue barriers to access evidence-based care in addiction treatment.